Embracing Digital Tools: Understanding Teachers' Attitudes on ICT Integration in Classroom Learning - Charisma, Dila; Winarto, Eline Rozaliya; Raman, Arumugam; Sirniawati; Jahni, Intan (Journal of Pedagogy and Education Science, 2025)
This qualitative research analyses the determinants that influence the attitudes of teachers toward integrating Information and Communication Technology (ICT) in teaching-learning. Based on the observation that teacher perception is the success factor of technology enhanced learning, this research would like to identify main drivers and barriers influencing ICT adoption. This study used qualitative methods to gather data, done through semi structured interviews and observing classrooms with 38 teachers of various subjects in different grade levels at a state junior high school in Indonesia and analysed the results thematically relating patterns and connections. Results show that teacher intentions to integrate ICT are affected by three main factors: usefulness, ease of use of digital resources and training in being able to make effective use of such resources, along with support at an infrastructural level. Teachers who attended in-service training and were supported by the institution as they integrated ICT became more self-assured and able to incorporate ICT tools that made it possible for them to be successful teachers. In contrast, obstacles including lack of infrastructure, time limitations and the absence of administrative support were identified as obstacles to successful implementation. The study concludes that enhancing teachers’ positive attitudes toward ICT requires targeted professional development programs, supportive leadership, and equitable resource distribution. These findings have practical implications for schools, teacher education institutions, and policymakers committed to fostering inclusive and sustainable ICT integration within the education system.